Linguistic functions and indirect speech acts in tobacco products health warnings - Julia Koszmider (Research in Language)
The study incorporates the theory of linguistic functions (Jakobson 1960) and speech act theory (Austin 1962) to analyse the differences and similarities of the language used to produce health warning signs on tobacco-related products in Polish and English. The analysis is based on the premise that labels have a primary force of being a warning, when their social function is in focus. The texts proposed as health warnings are highly formulaic and despite the fact that they address a variety of issues, they seem to be inherently similar in form. This pilot study aims to analyse corpora of selected Polish and English health warnings in order to assess the level of their linguistic similarity.